Incidence of Alternaria Species on Different Cereals, Pulses and Oil Seeds - Ashok M. Chavan, Sulochana R. Rathod* and (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Present paper deals with the study of diversity of Alternaria species on different cereals, pulses and oilseeds. Total nine species of Alternaria viz A. alternata, A. crassa, A. cihhorii, A. chrysanthemi, A. dianthicola, A. longipes A. porri, A. tenuissima and A. triticina were isolated from cereals like wheat, bajra, maize, barley and jowar . Eight species of Alternaria viz A. alternata, A. dianthicola, A. longipes, A. longissima, A. raphani, A. porri, A. sesame and A. tenuissima were reported on the pulses viz green gram, black gram, pea, red gram, cowpea and moth bean. Thirteen species of Alternaria like A. alternata, A. brassicicola, A. brassicae, A. carthami, A. helianthi ,A. longipes, A. longissima A. macrospore, A. ricini, A. raphani, A. sesame, A. sesamicola and A. tenuissima were occurred on six oil seeds like cotton, ground nut, sunflower, safflower, mustard and sesame.